Phylogenetic diversity based on 16S rRnA gene sequence analysis of aerobic thermophilic endospore-forming bacteria isolated from geothermal springs in Armenia - H. H. Panosyan (ՀՀ ԳԱԱ հրատ.)
Nineteen thermophilic aerobic endospore-forming bacteria were isolated from Armenian terrestrial hot (Arzakan) and warm (Akhourik) geothermal springs. The phylogenetic and taxonomic diversity of isolates was studied by the 16S rRNA gene (16S rDNA) analysis. The comparison of generated 16S rDNA sequences of the isolates with the ones available in GenBank database indicates their relation to phylum Firmicutes, subphylum Clostridium-Bacillus, group of Bacillus-like genera. The isolates are related to eleven species distributed in five genera: Bacillus, Geobacillus, Sporosarcina, Paenibacillus, and Thermoactinomyces. The thermophilic endospore-forming microflora was less diverse in the Akhourik spring and included representatives of genera Bacillus and Thermoactinomyces, with predominance of Bacillus species. Representatives of the genus Geobacillus were prevailing in the hot spring, in total constituting 50% of the detected isolates. Հայաստանի տաք (Ախուրիկ) և ջերմային (Արզական) հանքային աղբյուրներից մեկուսացվել են տասնինը թերմոֆիլ աերոբ էնդոսպոր առաջացնող բակտերիաներ և ըստ 16S ռՌՆԹ-ի գենի (16S ռԴՆԹ) նուկլեոտիդային հաջորդականությունների վերլուծության ուսումնասիրվել է դրանց տաքսոնոմիական և ֆիլոգենետիկական բազմազանությունը: Մեկուսացված կուլտուրաների 16S ռԴՆԹ-ի նուկլեոտիդային հաջորդականությունների համեմատումը GenBank-ի տվյալների բազայում առկա հաջորդականությունների հետ հաստատել է դրանց պատկանելիությունը Firmicutes ֆիլումին, Clostridium-Bacillus ենթաֆիլումին, Bacillus և ազգակից ցեղեր խմբին: Մեկուսացված շտամները նույնականցվել են որպես 11 տեսակներ` բաշխված Bacillus, Geobacillus, Sporosarcina, Paenibacillus և Thermoactinomyces ցեղերում: Թերմոֆիլ էնդոսպոր առաջացնող միկրոֆլորան Ախուրիկի հանքային աղբյուրում քիչ բազմազան է և ներառում է Bacillus և Thermoactinomyces ցեղերի ներկայացուցիչներ` Bacillus ցեղի տեսակների գերակշռմամբ: Geobacillus ցեղի տեսակները գերակշռում են ջերմային աղբյուրում` կազմելով մեկուսացված տեսակների 50%: Из наземных теплых (Ахурик) и горячих (Арзакан) геотермальных источников Армении изолированы девятнадцать термофильных аэробных эндоспорообразующих бактерий. На основании анализа гена 16S рРНК (16S рДНК)изучено их филогенетическое и таксономическое разнообразие. Сравнение последовательностей 16S рДНК изолятов с нуклеотидными последовательностями базы данных GenBank’а указывает на их принадлежность к филуму Firmicutes, к подфилуму Clostridium-Bacillus, к группе Bacillus с родственными родами. Изоляты отнесены к 11 видам пяти родов: Bacillus, Geobacillus, Sporosarcina, Paenibacillus, Thermoactinomyces. Термофильная эндоспорообразующая микрофлора менее разнообразна в теплом источнике и включает виды родов Bacillus и Thermoactinomyces, с доминированием представителей рода Bacillus. Представители рода Geobacillus доминируют в горячем источнике, составляя в целом 50% обнаруженных изолятов.
Keywords: Biology; Biochemistry